VOTING BEHAVIOUR AND ITS DETERMINANTS AMONG THE ELECTORS IN RURAL ASSAM: AN EMPIRICAL STUDY IN THE DHALPUKHURI DEVELOPMENT BLOCK OF THE HOJAI DISTRICT OF ASSAM - Islam, Saiful (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Voting behaviour is a vital aspect of the democratic process, revealing how and why electors exercise their franchise. Individual voting behaviour is influenced by social, economic, psychological, and political factors. In the context of rural Assam, this behaviour is embedded in a matrix of traditional structures, community influences, and emerging political consciousness. This study explores the patterns and determinants of voting behaviour among rural voters in the Dhalpukhuri Development Block of Hojai district, Assam. Using a combination of quantitative and qualitative approaches, this study examines how factors such as caste, religion, education, economic position, political awareness, local leadership, development ambitions, and media exposure influence the electoral decisions of rural voters. The study reveals a dynamic interplay between identity politics and performance-based evaluation, indicating a steady trend toward educated and independent political decisions among specific segments. The paper concludes with policy recommendations to promote democratic awareness and participatory governance at the grassroots level.